Religious polemics in context papers presented to the Second International Conference of the Leiden Institute for the Study of Religions (Lisor) held at Leiden, 27-28 April, 2000 - Hettema, Theo L.; Kooij, Arie van der (Studies in theology and religion, 2004)
Polemics, as "the art or practice of disputation or controversy", is a living issue in matters of religion, and is a major object of research for scholars in religious studies and theology. The second international conference of the Leiden Institute for the Study of Religions (LISOR), held at Leiden in April 2000, was devoted to the subject of Religious Polemics in Context, aiming at a further exploration of the notion of religious polemics, together with the unfolding of a wide variety of case-studies from various religious traditions. The volume contains most of the papers read at the conference, and offers contributions on general issues (e.g., by M. Dascal), as well as on particular topics in the fields of history of religion (e.g., Islam), ancient Israel and early Christianity, the history of Christianity, and the social sciences of religion. An annotated bibliography is added to this collection, which may stimulate a further study of the topic.